The Caprera Canyon (north–eastern Sardinia): A hotspot of cetacean diversity in the western Mediterranean Sea - Luca Bittau; Renata Manconi; Mariliana Leotta; Rossana Tenerelli; Mattia Cristina Leone; Elena Fontanesi; Federica Fonda; Ginevra Boldrocchi; Sandro Carniel; Rocco Tiberti (PLoS ONE, 2025)
The Caprera Canyon, a submarine canyon system off Sardinia in the western Mediterranean, was thought to be an important cetacean habitat, though studies on the area remained limited. To address this knowledge gap, 216 boat–based surveys were conducted between 2011 and 2019, covering 8443 km, using both research and whale–watching vessels. The distribution, diversity, relative abundance (Encounter Rate – ER), and habitat use of cetaceans were described, along with relevant behavioural and ecological observations. A total of 8 species were reported across 810 sightings, encompassing 7 out of the 8 cetaceans regularly found in the western Mediterranean Sea. These species, in order of relative abundance, include the striped dolphin (Stenella coeruleoalba), fin whale (Balaenoptera physalus), Cuvier’s beaked whale (Ziphius cavirostris), sperm whale (Physeter macrocephalus), Risso’s dolphin (Grampus griseus), common dolphin (Delphinus delphis), bottlenose dolphin (Tursiops truncatus), and a single observation of Sowerby’s beaked whale Mesoplodon bidens. This results in an overall ER of 10.6 sightings/100 km. ERs indicate that some species are particularly abundant in the study area, with Cuvier’s beaked whale registering one of the highest ER values ever documented in the Mediterranean Sea. Calves and behavioural observations suggest that the study area serves as both a breeding and feeding ground for most species. The high cetacean diversity and relative abundance, along with the regular occurrence of endangered and vulnerable species, identify the Caprera Canyon as an important hotspot for cetacean diversity. Habitat suitability models using the maximum entropy (MaxEnt) approach highlight that other smaller canyons surrounding the Caprera Canyon could provide suitable habitats for deep diving species. The results presented here serve as reference data for future studies on the ecology and long–term dynamics of cetaceans in the central–western Tyrrhenian Sea. We highlight that the Caprera Canyon and surrounding areas could benefit from being designated as an Important Marine Mammal Area (IMMA), potentially supporting conservation efforts, guiding marine spatial planning, and informing policy development to mitigate threats in the region.